Molecular insights into ion channel function (Review) - Doyle, D.A.
Water is probably the most important molecule in biology. It solvates molecules,all biochemical reactions occur in it and it is a major driving force in protein folding. Phospholipid membranes separate different water environments,but connections do exist between the different compartments. The integral membrane proteins (IMPs)form these connections. In the case of ions,IMPs form the passageways that regulate ion movement across the membrane. Structural information from three ion distinct channels are examined to see how these channels first select for and then control the movement of their target ions. This review focuses on how these channels select for target ions and control their movement while taking into account and using different properties of water. This includes the use of hydrophobic gates,mimick ing the water environment, and controlling ions indirectly by controlling water.
Keywords: CHANNEL; HYDROPHOBIC GATE; KIRBAC1.1; MSCL; ACETYLCHOLINE RECEPTOR